2017
DOI: 10.1002/chem.201701645
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Ligand Properties of Skeletally Substituted Cyclic (Alkyl)(Amino)Carbenes (CAACs) and Their Reactivity towards Small Molecule Activation: A Theoretical Study

Abstract: Quantum chemical calculations have been carried out to understand the ligand properties of skeletally modified cyclic alkyl amino carbenes. The stability of these carbenes has been assessed from an evaluation of their singlet-triplet and stabilization energy values. Ylide substituted carbenes are found to be more stable than non-ylidic ones in their optimized singlet state. Nucleophilicity and electrophilicity indices values were evaluated in order to further investigate the reactivity of these carbenes. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 102 publications
1
7
0
Order By: Relevance
“…Studies have also included comparison of carbenes with silylenes, germylenes, and abnormal carbenes, 179,183 analysis of ring size and heterocycles on carbene properties, 180 the introduction of boron substituents to (NHC and PHC) backbones, 157 the effect of additional rings and carbonyl substituents on normal and abnormal NHCs, 158 analysis of remote carbenes, 182,184 consideration of adduct formation for normal and abnormal NHCs, 181 and small molecule activation by cyclic (alkyl)(amino) carbenes (CAACs). 185 Overlap with our core set of carbenes (Table 1c) is quite poor as these studies have been focused on novel/unusual structures, so data have not been compiled in this case. These studies also reported a number of additional descriptor and energy calculations, allowing orbital analysis, predicting redox potentials, metal and fragment binding energies, nucleophilicity, electrophilicity, proton affinity, assessing aromaticity through nucleus independent chemical shifts (NICS 186 ) etc., as well as a range of calculated NMR data to assess different ligand structures.…”
Section: Ligand Knowledge Base (Lkb-c)mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also included comparison of carbenes with silylenes, germylenes, and abnormal carbenes, 179,183 analysis of ring size and heterocycles on carbene properties, 180 the introduction of boron substituents to (NHC and PHC) backbones, 157 the effect of additional rings and carbonyl substituents on normal and abnormal NHCs, 158 analysis of remote carbenes, 182,184 consideration of adduct formation for normal and abnormal NHCs, 181 and small molecule activation by cyclic (alkyl)(amino) carbenes (CAACs). 185 Overlap with our core set of carbenes (Table 1c) is quite poor as these studies have been focused on novel/unusual structures, so data have not been compiled in this case. These studies also reported a number of additional descriptor and energy calculations, allowing orbital analysis, predicting redox potentials, metal and fragment binding energies, nucleophilicity, electrophilicity, proton affinity, assessing aromaticity through nucleus independent chemical shifts (NICS 186 ) etc., as well as a range of calculated NMR data to assess different ligand structures.…”
Section: Ligand Knowledge Base (Lkb-c)mentioning
confidence: 99%
“…Phukan and collaborators , have again used a range of descriptors to assess carbenes. While the exact selection varied with application and no single coherent database has been presented, capturing carbene properties across a wide range of structural modifications.…”
Section: Ligand Descriptorsmentioning
confidence: 99%
“…Besides the typical NHCs, stable cyclic alkyl-amino carbenes (cAACs) with stronger nucleophilic (σ-donors) and electrophilic (π-acceptors) character were first isolated and characterized by Bertrand and co-workers in 2005 . This unique electronic feature of cAAC has resulted in on ongoing “renaissance” in the stabilization of various unstable chemical species, radicals, and elements in their different unusual oxidation states. In recent years, the wider application of carbenes has emboldened many research groups worldwide in the exploration of new classes of carbenes with interesting electronic properties and novel catalytic activities. Few research studies have focused on both computational design and experimental isolation of novel carbenes, with the aim of achieving superior σ-donation and π-backdonation abilities compared to the reported analogues. On the other hand, the stabilization of main-group elements and transition metals in their unusual oxidation states employing these carbenes has become the primary focus in many research laboratories. In 2008, Robinson and co-workers isolated the silicon(0) compound featuring a SiSi double bond, revealing that NHCs could stabilize main group elements in their zero oxidation state . In subsequent years, the analogous Ge(0) and Sn(0) complexes were synthesized and isolated by Jones and co-workers utilizing NHC Ar (Ar = 2,6-diisopropylphenyl or 2,4,6-trimethylphenyl).…”
Section: Introductionmentioning
confidence: 99%
“…Here, one of the nitrogen substituents of an NHC was replaced by an ylide group. Due to the lower electronegativity of carbon compared to nitrogen, such an ylide-substitution should result in increased HOMO and LUMO levels, thus making CAYCs particularly strong donors with interesting electronic properties [20][21][22][23][24]. Eigenvalues of the frontier orbitals were taken from Reference [21].…”
Section: Introductionmentioning
confidence: 99%